Predoctoral dental implant education at King Abdulaziz University - Hind Ahmed Aljohani; Ali Saad Thafeed AlGhamdi (Elsevier, 2009)
Objective: In June 2008, a survey of freshly graduated dental students of King Abdulaziz University Jeddah was conducted to evaluate the extent of their exposure to oral implantology and their knowledge of some basic principles of dental implant treatment. Materials and methods: Multiple-choice questionnaires were given to the fresh graduate dental students of King Abdulaziz University Jeddah to answer. Sixty-six students responded out of 86, yielding a response rate of 76.7%. Results: Majority of the students (78.8%) thought that they did not have enough lectures about dental implants and all of them thought that they did not have enough training in dental implant. Most of the students were not familiar with different dental implant systems (61.1%), designs (60.6%) or sizes (74.2%). Majority of the students were lacking the knowledge about basic principles of dental implant treatment. At King Abdulaziz University, Faculty of Dentistry, implant dentistry is taught to the students in the form of implant-related lectures incorporated into their periodontic, oral surgery and prosthodontic courses with one or two lectures given on dental implant in each course. Conclusion: There is an urgent need to develop a well-structured implant course that includes didactic, laboratory, preclinical and clinical components at the undergraduate curriculum of King Abdulaziz University Faculty of Dentistry. Keyword: Implant dental education